2022
DOI: 10.1002/1873-3468.14330
|View full text |Cite
|
Sign up to set email alerts
|

The toxic effects of yeast Ppz1 phosphatase are counteracted by subcellular relocalization mediated by its regulatory subunit Hal3

Abstract: Overexpression of Saccharomyces cerevisiae protein phosphatase Ppz1 strongly impairs cell growth. Ppz1 is negatively regulated by its subunit Hal3, and Hal3 overexpression fully counteracts the toxic effects derived from high levels of the phosphatase. We show that Ppz1 localizes at the plasma membrane, and that co‐expression of Hal3 recruits Ppz1 to internal membranes (mostly vacuolar). This effect is not observed in a catalytically impaired mutant of Ppz1. Disruption of intracellular trafficking by deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
(76 reference statements)
0
10
1
Order By: Relevance
“…Thus, the simplest scenario was that Hal3 interacts with the excess of Ppz1 and inhibits its phosphatase activity, thus avoiding harmful dephosphorylation of key cellular targets. However, we have found very recently [81] that episomal expression of Hal3 in cells overexpressing Ppz1 triggers the translocation of the phosphatase from the plasma membrane to intracellular structures that could be identified as the vacuolar membrane and, less often, the endoplasmic reticulum. Colocalization experiments showed that Hal3 accompanies Ppz1 in these intracellular locations.…”
Section: Hal3: Just An Inhibitor Of Ppz1 Activity?mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the simplest scenario was that Hal3 interacts with the excess of Ppz1 and inhibits its phosphatase activity, thus avoiding harmful dephosphorylation of key cellular targets. However, we have found very recently [81] that episomal expression of Hal3 in cells overexpressing Ppz1 triggers the translocation of the phosphatase from the plasma membrane to intracellular structures that could be identified as the vacuolar membrane and, less often, the endoplasmic reticulum. Colocalization experiments showed that Hal3 accompanies Ppz1 in these intracellular locations.…”
Section: Hal3: Just An Inhibitor Of Ppz1 Activity?mentioning
confidence: 99%
“…Translocation of Ppz1 to internal membranes is a crucial event for the ability of Hal3 to counteract Ppz1 toxicity. Indeed, mutation of the VPS27 gene aggravated the cell growth defect even when Ppz1 was overexpressed at moderate levels and greatly impaired the ability of Hal3 to normalize the growth of these cells [81]. VPS27 encodes a component of the ESCRT-0 complex required for various cellular functions, including the trafficking of membrane proteins to the vacuole for degradation [82].…”
Section: Hal3: Just An Inhibitor Of Ppz1 Activity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Ppz1 is normally found at the cell periphery, likely attached to the plasma membrane because of its conserved myristoylated Gly2, and the beneficial effect of Hal3 overexpression was thought to derive from the blocking of the phosphatase activity at the normal Ppz1 cellular location. However, recent work by Albacar and coworkers [ 48 ] showed that, in Ppz1-overexpressing cells, Hal3 recruits the phosphatase to internal membranes (mostly vacuolar) and that such intracellular trafficking is crucial to normalize growth. Interestingly, removal of the Hal3′s 90 KRVPAVTFS 98 motif described above also affects, even moderately, both Ppz1 intracellular relocalization and counteraction of toxicity in cells overexpressing the phosphatase.…”
Section: Structural Insights Into the Moonlighting Functions Of Hal3mentioning
confidence: 99%